Liquid–liquid phase separation underpins the formation of replication factories in rotaviruses. (15th September 2021) - Geiger, Florian; Acker, Julia; Papa, Guido; Wang, Xinyu; Arter, William E; Saar, Kadi L; Erkamp, Nadia A; Qi, Runzhang; Bravo, Jack PK; Strauss, Sebastian; Krainer, Georg; Burrone, Oscar R; et al.
Abstract: RNA viruses induce the formation of subcellular organelles that provide microenvironments conducive to their replication. Here we show that replication factories of rotaviruses represent protein‐RNA condensates that are formed via liquid–liquid phase separation of the viroplasm‐forming proteins NSP5 and rotavirus RNA chaperone NSP2. Upon mixing, these proteins readily form condensates at physiologically relevant low micromolar concentrations achieved in the cytoplasm of virus‐infected cells. Early infection stage condensates could be reversibly dissolved by 1, 6‐hexanediol, as well as propylene glycol that released rotavirus transcripts from these condensates. During the early stages of infection, propylene glycol treatments reduced viral replication and phosphorylation of the condensate‐forming protein NSP5. During late infection, these condensates exhibited altered material properties and became resistant to propylene glycol, coinciding with hyperphosphorylation of NSP5. Some aspects of the assembly of cytoplasmic rotavirus replication factories mirror the formation of other ribonucleoprotein granules. Such viral RNA‐rich condensates that support replication of multi‐segmented genomes represent an attractive target for developing novel therapeutic approaches. Synopsis: Early replication factories provide a microenvironment for replication of RNA viruses. Here, rotavirus replication factories are found to represent protein/RNA‐rich condensates formed by liquid‐liquid phase separation (LLPS), whose disruption hampers viral replication. Rotavirus viral replication factories, or viroplasms, are formed via liquid‐liquid phase separation of the non‐structural scaffold protein NSP5, and the RNA chaperone NSP2. Early infection‐stage viroplasms are liquid‐like protein droplets that recruit rotavirus RNA, while late infection‐stage viroplasms lose their liquid‐like properties upon maturation. Viroplasms can be dissolved by LLPS‐disrupting propylene glycol during early infection stage, causing reduction in viral replication, concomitant with NSP5 dephosphorylation. Compounds that disrupt viroplasms by shifting the phase boundary of NSP5/NSP2 condensates may be exploited in future antiviral strategies. Abstract : Viroplasms represent protein/RNA‐rich condensates formed by phase‐separation of NSP2 and NSP5 proteins, whose disruption by chemical compounds reduces rotavirus replication.